Social butterflies - Horn, Henry S., 1941-2019 (Monographs in population biology., 2021)
"Throughout his career, Henry Horn developed a unique approach to the study of butterflies. In this book, he brings together his research with recent findings to present the most recent account of social butterflies-that is, butterflies whose interactions are sufficiently complex as to resemble the level of organization and communication typically associated with vertebrates and some bees. The core of the book consists of focused studies of five species: the Plain Ringlet, Eyed Brown, Great-Spangled Fritillaries, Viceroy, and Pearly Eye, in order of increasing complexity of social interaction. In each chapter, Horn presents a descriptive account of the species' natural history and behavioral idiosyncrasies, ranging behavior, and a model to explain a characteristic aspect of its behavior. He then proceeds to emphasize key departures from these models in order to present the hypothesis that some butterflies make decisions-that is, they are not simply pre-conditioned to react to stimuli in a certain way-by looking at how butterflies interact with the landscape and each other. The book ends with a summary of key conclusions as well as a list of intriguing but yet unanswered questions in need of future research"--